2000
DOI: 10.1067/mhn.2000.104949
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Lower Lip Defects aFter Tumor Excision: An Aesthetic and Functional Evaluation

Abstract: We are presenting a new questionnaire to evaluate the functional and aesthetic aspects after reconstruction of defects of the lower lip resulting from tumor excision. The questionnaire is based on objective parameters with numerical values. The application of the questionnaire is carried out based on 2 different surgical techniques, which have been used in the Department of Oral and Maxillofacial Surgery of La Princesa University Hospital in Madrid. These techniques are used in the reconstruction of surgical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Only few functional evaluations with objective parameters have been found in the literature on reconstructive surgery of the lip [13,19], thus allowing no valuable comparison of our results with those of other authors. Three out of 24 patients presented a postoperative hindering microstomy secondary to a postoperative dehiscence in two cases and to an improper use of the technique in one case (tumor size too large to perform a Meyer's plasty).…”
Section: Discussionmentioning
confidence: 96%
“…Only few functional evaluations with objective parameters have been found in the literature on reconstructive surgery of the lip [13,19], thus allowing no valuable comparison of our results with those of other authors. Three out of 24 patients presented a postoperative hindering microstomy secondary to a postoperative dehiscence in two cases and to an improper use of the technique in one case (tumor size too large to perform a Meyer's plasty).…”
Section: Discussionmentioning
confidence: 96%
“…A search for relevant studies revealed 432 studies, of which six met inclusion criteria and had disease-specific items relevant to lip dysfunction (Fig 1). 1,10,14,15,20,21 Further items were generated on the basis of expert opinion. Two subscales, consisting of a 15-item patient rated subscale and a four-item external rater subscale, were created (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…Its compliance with the lines of tension of the lower one-third of the face, the creation of a neo-vermilion and its wide design provide a satisfactory and symmetric esthetic result that is also functional, while avoiding the risk of microstomia. Compared to the Colmenero flap, the Yu flap involves a higher level of technical difficulty and a smaller supply of tissue, but better aesthetic acceptance and equal or greater lip closure 13 . In our experience, the final functional and aesthetic results of the Colmenero flap were satisfactory in all cases, even if half of patients required surgical retouching at a second stage.…”
Section: Discussionmentioning
confidence: 99%